Analysis of the Effect of Job Satisfaction on Organizational Commitment and Teacher Performance During the COVID-19 Pandemic (Study at the Darud Da'wah Wal-Irsyad Foundation, Batulicin District, Tanah Bumbu Regency) - Mulyadi, Andi; Meiske Claudia (HM Publisher, 2022)
This study aims to determine and analyze the effect of job satisfaction (X1) on organizational commitment (Z) and teacher performance (Y) at the Darud Da' Wah Wal-Irsyad Education Foundation, Batulicin District, Tanah Bumbu Regency. This research used a questionnaire with 85 teachers at the Darud Da'wah Wal-Irsyad Education Foundation, Batulicin District, Tanah Bumbu Regency. Samples were determined using the saturated sampling technique, where all of the population was used as research samples. The data were analyzed using the partial least square (PLS) method in three stages: evaluation of the outer model, inner model, and hypothesis testing, hypothesis testing using the t-statistical test. The results showed that there was a significant effect between job satisfaction and teacher organizational commitment, there was a significant effect between job satisfaction on teacher performance, there was a significant effect between organizational commitment on teacher performance, there was a mediating effect of organizational commitment through job satisfaction on teacher performance at the Darud Da'wah Wal-Irsyad Education Foundation, Batulicin District, Tanah Bumbu Regency.